ANALISIS PEKERJAAN DAN PERENCANAAN SUMBER DAYA MANUSIA SERTA PENGARUHNYA TERHADAP METODE REKRUTMEN - Novie P. Marhaeni (Politeknik Ubaya, 2019)
Human resources and jobs are an inseparable unit in a company. Both go hand in handand have high dependency. Company management needs to do a job analysis along with human resource planning that will fill the formation or do the work. Therefore, job analysis and HR planning provide direction for management to determine the right method in the recruitment process. Thus, they can get the right people to fill the right position too. This article aims to examine and explain the effect of job analysis and HR planning on recruitment methods. With the literature study conducted, it was concluded that both the job analysis and HR planning variables have a significant influence on the recruitment method.